What is the rate of venous thromboembolism (VTE) in women taking combined oral contraceptives (COCs)?. Issue 2 (February 2017) - Lauder, Travis; LaMaster, Zachary
Abstract : EVIDENCE‐BASED ANSWER : The rate of VTE in women taking COCs is approximately 0.06% per year. Third‐generation and newer progestins (norgestimate, desogestrel, gestodene, drospirenone, and cyproterone acetate) are associated with greater risk of VTE (about 0.1% per year) (SOR: B, consistent findings from cohort studies).